Penerapan Metode Analytic Network Process (ANP) dalam Menentukan Peringkat Kinerja Dosen - Bambang Cahyono; Muhammad Farman Andrijasa; Tommy Bustomi (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2024)
The use of the Analytic Network Process (ANP) method in evaluating and ranking lecturer performance. ANP is a complex decision-making method that allows the assessment of various interrelated factors in a network. In the context of higher education, evaluating lecturer performance is very important because the quality of teaching and lecturers' contribution to research and scientific development has a direct impact on students' learning experience and institutional reputation. However, assessing lecturer performance is not an easy task because it involves a variety of complex and interrelated factors, such as teaching ability, research contribution, community service, and various other administrative aspects. The results of this study show that the ANP method has proven to be effective and successful in providing an objective, structured, and detailed description of lecturer performance. The results can be used to support decisions regarding awards, promotions, or training needed to achieve better overall performance with a 70% success rate in assessing lecturer performance.